Kuleana and commitment : working toward a collaborative Hawaiian archaeology - Kawelu, Kathleen L. (University of Hawaiʻi Press, 2015)
The sociopolitical climate of Hawai'i has changed substantially in recent decades, and archaeologists working to decipher the islands' past are increasingly faced with a complexity of issues involving Kanaka Maoli (Native Hawaiian) concerns. Among these are the push for sovereignty; cultural perpetuation and revitalization; legal challenges to Kanaka Maoli programs, such as Hawaiian Home Lands and the Office of Hawaiian Affairs; and compliance with the Native American Graves Protection and Repatriation Act (NAGPRA). In Kuleana and Commitment, Kathleen L. Kawelu examines the entangled interactions between Kanaka Maoli and archaeologists in Hawai'i by conducting an ethnographic investigation of the discipline of archaeology itself. She explores the development of Hawaiian archaeology, discusses important cases of the recent past, and focuses on the interpersonal relationships between these two key groups involved in heritage management in Hawai'i. By revealing and understanding the contemporary attitudes of Kanaka Maoli and archaeologists toward each other, Kawelu suggests a change in trajectory toward a more collaborative approach in practicing Hawaiian archaeology. Through interviews with individuals from both communities, Kawelu taps into collective narratives that reveal two overarching themes. The first narrative speaks about the continuation of Kanaka Maoli cultural practices and beliefs, for example, kuleana (responsibility); the second speaks about the kind of commitment to Hawaiian archaeology and Kanaka Maoli descendants that is desired from archaeologists. Requests for respect, communication, and partnership are heard in the narratives. These same qualities also serve as the foundation for community-based archaeology, which challenges the exclusive access of archaeologists to the past and places the discipline and its practitioners among a broader group of stakeholders, particularly descendant communities.